ANALISIS WILLINGNESS TO PAY (WTP) DAN KEBUTUHAN AIR DI KECAMATAN MERAWANG - Fadillah Sabri; Ririn Amelia (Universitas Lambung Mangkurat, 2016)
The population growth and diversity of activities in the community in various fields occasion requirement of water have an important issue. Especially, supply of clean water. However, the availability of water in the Merawang Subdistrict had occurs dryness cause by drought in the 2015. Finally, many people using services from the Water Supply Company (PDAM) Tirta Bangka, Merawang Subdistrict. This indicated that there is a high ability and willingness of people to pay for services of PDAM. Therefore, in this research aims to examine the relationship between Willingness to Pay (WTP) of clean water in PDAM with the urgent water needs. Type of research is quantitative research, which is located in four villages in the Merawang Subdistrict. Such as Baturusa village, Riding Panjang village, Dwi Makmur (Sunghin) village, and Merawang village. In this case, we use Contingent Valuation Method (CVM) which using questionnaires and interviews to respondents in the village. The results of research showed that the rates paid by people who are willing to be in the range of Rp.50000.00/month until Rp.99000.00/month, average Rp.73378.00/month. Based on the results, tariff of WTP is Rp.2197.00/m3. In addition, from the analysis obtained the PDAM Tirta Bangka in Merawang was installed capacity of 10 l/s and water needs in the four villages, which is constitute the PDAM service area of less than 10 l/s. This suggests that the capacity of Water Supply Company (PDAM) Tirta Bangka has enough supplies for 10 years in Merawang Subdistrict.